Optimalization of VAI Screening Policy: Implementation of Permenkes No. 29/2017 in Improving Early Detection of Cervical Cancer in Indonesia - Desriani, Ririn; Febryanti, Indira Puspa; Puspitasari, Sepsiana (BKM Public Health and Community Medicine, 2024)
Background: Cervical cancer remain a global health problem that causes death in 9 out of 10 women with cervical cancer in developing countries, also the second most common disease among women in Indonesia. Purpose: To provide recommendations for policy implementation programs to increase coverage of Visual Inspection of uternie cervix with Acetid acid (VIA) screening. Methods: A narrative analysis research using inductive document collection, presented in themes. Results: Rencana Aksi Nasional (RAN) Eliminasi Kanker Leher Rahim 2023-2030 specifies HPV DNA as the primary screening method for cervical cancer. This method is considered more expensive, not covered by social health insurance administration body (BPJS), and there are limited health officer who can deliver the screening. Crossline with Permenkes No. 29 Tahun 2017 article 1 paragraph 2, which stipulates the VIA method as the main one. However, there is a disparity in the national target and achievement of national VIA screening (70% target, 9.3% coverage) by 2022. This raises the urgency of developing a special program to increase cervical cancer screening through the VIA method. Conclusions: There is a necessary to adjust policy implementation through special programs to increase the coverage of screening by VIA method in Indonesia.